YAREN: Humanoid Torso Robot Platform for Research, Social Interaction, and Educational Applications - Daniela Sanchez-Orozco; Rhandall Valdez; Yandri Uchuari; Marcelo Fajardo-Pruna; Luis Cavazos Quero; Redhwan Algabri; Emiliano Quinones Yumbla; Francisco Yumbla (IEEE Access, 2025)
In the pursuit of maximum efficiency and performance, robots are often designed with complex functionalities and mechanisms customized for specific applications. These designs are frequently proprietary, limiting their adoption by the research community for experimentation. This work introduces YAREN, an open-source humanoid torso robot for social and educational applications. We modeled YAREN’s anatomy based on anthropometric measurements, considering dimensions and mobility limitations, to promote more friendly and natural interactions with its end-users. YAREN has 12 degrees of freedom which allows it to perform a wide variety of movements, generating more realistic and dynamic interactions. Executing broader and more expressive poses enables more efficient and meaningful social communication with users. The electronic components were selected for availability and robustness, ensuring the robot’s structure moves without complications. Relatively low-cost components were selected to provide a high-quality product that remains accessible to multiple laboratories, even in resource-limited contexts. YAREN’s software is based on the Robot Operating System (ROS) to facilitate expansion and scalability. We also provide the kinematic model and tuning of the PID controller for the motors to control each joint precisely and optimize movement without compromising user safety. Based on our proposed open-source design, YAREN can be expanded to perform diverse interactive functions for social and educational purposes, promoting the research and development of humanoid robots. We hope our design can be replicated by researchers worldwide to support multiple projects and help grow more laboratories.